A hybrid electrochemical flow reactor to couple H2 oxidation to NADH regeneration for biochemical reactions. Issue 4 (29th May 2021) - El Housseini, Wassim; Lapicque, François; Walcarius, Alain; Etienne, Mathieu
Abstract: Beta‐nicotinamide adenine dinucleotide (NAD + /NADH) is an important enzymatic co‐factor that can be efficiently regenerated using a rhodium‐based catalyst as electron transfer mediator ( ie, [Cp*Rh(bpy)Cl] +, where Cp* = pentamethylcyclopentadienyl and bpy = 2, 2‐bipyridine). Here, the above mediated regeneration of NADH is implemented in a redox flow bioreactor hybridized with a gas diffusion electrode for hydrogen oxidation. The reactor was initially optimized with respect to rhodium complex and NAD + concentrations, humidification of the hydrogen gas, flow rates of both H2 gas and electrolytic solution, and solution pH. The integration of an enzymatic reaction consuming the generated NADH was then investigated in a flow process, combining in series the electrochemical reactor to a biochemical cell with immobilized l ‐lactic dehydrogenase for the conversion of pyruvate to lactate. A high activity was achieved with a turnover number up to 370 h −1 for NADH regeneration. Coupled electrochemical regeneration to enzymatic reaction led to total turnover number values of 2000 and 6.3 × 10 6 for NADH electrochemical regeneration and bioconversion, respectively.